A novel methodology for hydrogel water content determination by EPR: The basis for real-time monitoring of controlled drug release and hydrogel swelling and degradation. (June 2021) - Vesković, Ana; Nakarada, Đura; Popović Bijelić, Ana
Abstract: The hydrogel water content is of fundamental importance for controlled drug delivery, as it influences the overall hydrogel integrity and solubility, as well as the diffusion kinetics of substances. This work describes a new methodological approach for hydrogel water content determination using electron paramagnetic resonance (EPR), a highly sensitive spectroscopic technique. It is based on the idea that an EPR active molecule ( i.e. spin probe), that is dissolved in the water phase of the hydrogel and does not interact with the polymer matrix, is a reliable water content reporter. The proposed novel methodology is cost-effective, and independent of the gel type, size or viscoelastic properties. Furthermore, it allows for the visualization of the hydrogel by 2D/3D EPR imaging, and may be further developed for real-time monitoring of hydrogel swelling and degradation, as well as controlled drug release. Graphical abstract: Image 1 Highlights: A novel methodology for hydrogel water content assesment using EPR is proposed. The EPR visible 3-carbamoyl-PROXYL is a confident reporter of hydrogel water content. EPR imaging reveals hydrogel size and shape during hydrogel swelling/degradation. The proposed method is adequate for controlled drug release investigations in vivo.